2011
DOI: 10.1016/j.anr.2011.09.005
|View full text |Cite
|
Sign up to set email alerts
|

Breast Cancer Screening Practice and Health-Promoting Behavior Among Chinese Women

Abstract: On the basis of these results, public education about importance of breast cancer screening and health promoting behavior should be strongly advocated by health professionals and mass media in China.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

10
37
2

Year Published

2013
2013
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 26 publications
(49 citation statements)
references
References 12 publications
10
37
2
Order By: Relevance
“…Data from the United States showed that the mammography screening rates (36-67%) among the ethnic minorities have been observed to be the lowest in Asians ( Lee-Lin et al, 2007). Similarly, in a parent study of this current paper on Chinese women in China, the rates of regular mammographic screening varied between regions from 4.8-28.8% (Kim et al, 2011). Previous studies explained sociocultural and individual beliefs and perceptions to be associated with mammography adherence (Carney et al, 2002;Chua et al, 2005;Wang et al, 2009;Lee et al, 2010).…”
Section: Factors Associated With Mammography Adherence Among Married mentioning
confidence: 55%
See 4 more Smart Citations
“…Data from the United States showed that the mammography screening rates (36-67%) among the ethnic minorities have been observed to be the lowest in Asians ( Lee-Lin et al, 2007). Similarly, in a parent study of this current paper on Chinese women in China, the rates of regular mammographic screening varied between regions from 4.8-28.8% (Kim et al, 2011). Previous studies explained sociocultural and individual beliefs and perceptions to be associated with mammography adherence (Carney et al, 2002;Chua et al, 2005;Wang et al, 2009;Lee et al, 2010).…”
Section: Factors Associated With Mammography Adherence Among Married mentioning
confidence: 55%
“…Despite of the incidence rate among Western countries have been increasing in 1980s and 1990s due to routinely use of mammography (Jemal et al, 2011) but the death rate have been decreasing over the past 25 years due to improved early treatment. In contrast, the lower survival rate of breast cancer has been found in Asian countries including China (Kim et al, 2011).…”
Section: Introductionmentioning
confidence: 93%
See 3 more Smart Citations